Foreign Bodies in the Eyes, Ears, Nose and Throat - Powell, D. Gregory (1981)
This article outlines the presenting problems of foreign bodies in the eyes, ears, nose and throat, describing diagnostic signs associated with each common type of foreign body presentation and the methods involved in removal. Equipment and supplies for the average emergency room are listed according to location of the foreign body.